2021
DOI: 10.4236/jep.2021.129038
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Heavy Metals in Food Crops at Abandoned Lead-Zinc Mining Site at Tse-Faga, Logo, Lga, Benue State, Nigeria

Abstract: Hundreds of children died in 2010 due to suspected lead poisoning from mining sources in Zamfara State among epidemiological concerns. Evaluating ecological and human health risks of heavy metals levels in sampled food crops harvested near two abandoned Lead-Zinc mining sites at Logo Benue State is crucial. Abelmoschus esculentus, Carica papaya, Manihot esculenta, and Zea mays were sampled, prepared, and analyzed for four heavy metals using the Atomic Absorption Spectrophotometric method. The mean data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Evaluation of heavy metals in a Nigeria river, Southeast Nigeria, showed that hazard index for Pb and Cd far exceeds threshold value (Anyanwu and Nwachukwu, 2020). Also, findings from health risk assessment in Benue State, Nigeria, indicates that communities around mining areas may be at risk of Pb poisoning due to high contamination of food samples in the studied communities (Samuel and Babatunde, 2021).…”
Section: Effects Of Heavy Metals Pollution On Food Safety and Securitymentioning
confidence: 88%
“…Evaluation of heavy metals in a Nigeria river, Southeast Nigeria, showed that hazard index for Pb and Cd far exceeds threshold value (Anyanwu and Nwachukwu, 2020). Also, findings from health risk assessment in Benue State, Nigeria, indicates that communities around mining areas may be at risk of Pb poisoning due to high contamination of food samples in the studied communities (Samuel and Babatunde, 2021).…”
Section: Effects Of Heavy Metals Pollution On Food Safety and Securitymentioning
confidence: 88%
“…A widely used acid-based digestion method was used for the plant sample digestion (Alain et al 2021;Blum et al 1996;Samuel and Babatunde 2021). Briefly, one gram of the oven-dried sample was weighed into a 100 mL beaker, followed by the addition of 10 mL of concentrated HNO 3 (analysis grade, Merck-Germany) and 2 mL concentrated HClO 4 (Merck-Germany).…”
Section: Digestion Of the Samplementioning
confidence: 99%
“…Mining has long been associated with the release of a range of toxic metals including lead (Pb), found at high levels in land surrounding mine dumps and far afield. Research has documented high levels of Pb in water sources associated with solid mineral mining operations in different world regions [1][2][3][4]. Chronic human exposure to Pb in water can lead to accumulation in human blood and elevated blood lead levels (BLLs).…”
Section: Introductionmentioning
confidence: 99%